THE CONSERVATION OF MARINE ECOSYSTEM FROM TRAWL USAGE BY THE LOCAL GOVERNMENT BASED ON SUSTAINABLE MARINE PRESERVATION PRINCIPLE - Waluyo, Waluyo; Winarno, Djoko W.; Kusumo, Ayub T. S.; Candrakirana, Rosita (UI Scholars Hub, 2017)
Fisheries practice using trawl and seine nets in Indonesia are still numerous since fishermen round that it will yield much more. However, the practice also threatens the life of small and young fishes as well as destroys the coral reef. The government then issued the regulation namely the Regulation of Minister on Marine Affairs and Fishery Number 2/Permen-KP/2015 about the Prohibition of Trawl and Seine Nets Usage which apply to the whole area of fisheries in Indonesia. It was one of the efforts by the Government of the Republic of Indonesia in conserving its marine ecosystem. The aim of this study was to evaluate the application of regulation to prohibit the trawl and seine nets usage based on sustainable marine preservation principle. This study was a doctrinal research applying case approach and statute approach. The study was held on several regions in Indonesia where the regulation has been enforced. The findings then elaborated with legal sources, such as Act number 32 year 2009 about Environment Conservation and Management, Act number 31 year 2004 about Fisheries, and Regulation of Minister of Marine and Fishery Number 2/Permen-KP/2015 as primary legal sources. The secondary legal sources used were journals, articles, and other relevant sources. The result showed that there is a need to establish a model for ideal implementation of the regulation based on sustainable marine preservation principle in order to conserve the marine environment as well as to increase the welfare of traditional fishermen.